2021
DOI: 10.1016/j.jsps.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factors influencing pharmacy interns career choices in Saudi Arabia

Abstract: Background The number of students enrolled in the colleges of pharmacy in Saudi Arabia is high, and the number of pharmacy graduates expected to join the workforce in the coming years is expected to grow. There are limited number of studies that assess factors influencing pharmacy students’ career choices in Saudi Arabia in the literature. The aim of this study was to assess the factors that influence career goals and to investigate students’ perceptions about their career goals. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…On the other hand, a high proportion of males showed a preference to working as medical sales representatives (13%), compared to females (1.6%). This finding agrees with reports from Jordan [8], and Saudi Arabia [38], where the influence of gender on future career choice was observed and attributed to cultural and social reasons [38]. Fieldwork, outstation trips, night shifts, and weekend hours that may be required to complete tasks, make the medical representative position more appealing to men [8].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, a high proportion of males showed a preference to working as medical sales representatives (13%), compared to females (1.6%). This finding agrees with reports from Jordan [8], and Saudi Arabia [38], where the influence of gender on future career choice was observed and attributed to cultural and social reasons [38]. Fieldwork, outstation trips, night shifts, and weekend hours that may be required to complete tasks, make the medical representative position more appealing to men [8].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the study also found that curriculum content was another major influencing factor (70%) unlike our study that found that such factor had an impact on career choice of only 17.8% of the participants. A study from a large pharmacy college in Saudi Arabia found that work environment, advancement opportunities, and salary were the major factors influencing career choices [6]. Studies from Saudi Arabia and China demonstrated that salary, advancement opportunities, and a motivating environment for growth were particularly important to males, whereas a flexible and stable workplace was important to females [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another single-institution study done in 2017 showed that the preferred career pathway for Saudi female pharmacy students was hospital pharmacy in government hospitals (50.9%) followed by academia (19.4%), whereas community pharmacy was the least preferred pathway [ 5 ]. Another single-institution study found that work environment, advancement opportunities, and salary were the most important factors guiding career selection [ 6 ]. Despite the interesting findings of these studies, none investigated the reasons or influencing factors behind the career choices made by the participants.…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by academia and research centres selected by 24.8%, whereas the pharmaceutical industry and community pharmacies were the least preferred selected by 7% and 2%; respectively. Nevertheless, a similar study conducted by Bannan et al (2021) , surveyed PharmD students in their last year (i.e., interns) in the academic year 2018–2019, found that the top ranked career goals of the interns were industry and drug company followed by clinical pharmacy. This finding reflects a change in the orientation among pharmacy students who are about to be graduated who would be reading the current situation and the future opportunities more carefully than the students from lower levels.…”
Section: Drivers For Improvements and Changesmentioning
confidence: 96%